Electronic Freight Exchange as a Tool to Support Enterprise Cost Management Based on Feedback from Trans.Eu Users - Sławomir SKIBA (Communications of International Proceedings, 2021)
In a research study by Othmani and Bouslama (2015) managing the transportation process requires effective tools which can be used, among other ends, to establish business relationships, conclude transactions and settle payments for services. Karaś (2020) and Klopott (2020) indicate, that all these and other needs are met by electronic freight exchanges. Although most businesses with extensive freight needs already use such services, it remains unclear whether they are driven by necessity or convenience. It is important to analyze whether electronic freight exchanges have any shortcomings hindering the transportation process, and if so, determine who is at the losing end of these drawbacks, where they stem from, and whether they can be reduced or remedied to better optimize freight management. Many articles highlight the mainly positive impact of electronic freight exchanges on transport-related processes, and only a few point out the pain points. Many businesses may either overlook or ignore these red flags, making it pivotal to identify and raise awareness among users about potential threats of electronic freight exchanges along with ways to mitigate them in order to best reap the benefits offered by such platforms. The article approaches electronic freight exchanges as an effective tool supporting freight management and helping optimize costs, including those related to environmental footprint. The aim of the article is to present and analyze the effectiveness of the Trans.eu platform and outline the actions that users should take to streamline their transport processes with as few side effects as possible.
Keywords: Electronic Freight Exchange; Cost Optimization; Freight Management